2013
DOI: 10.1186/1748-717x-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Increased radiosensitivity and radiothermosensitivity of human pancreatic MIAPaCa-2 and U251 glioblastoma cell lines treated with the novel Hsp90 inhibitorNVP-HSP990

Abstract: Background and purposeHeat shock Protein 90 (Hsp90) is a molecular chaperone that folds, stabilizes, and functionally regulates many cellular proteins involved in oncogenic signaling and in the regulation of radiosensitivity. It is upregulated in response to stress such a heat. Hyperthermia is a potent radiosensitizer, but induction of Hsp90 may potentially limit its efficacy. Our aim was to investigate whether the new Hsp90 inhibitor NVP-HSP990 increases radiosensitivity, thermosensitivity and radiothermosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…They bind to the N-terminal ATPase-pocket, affecting the chaperone activity and leading to the depletion of HSP90 substrates by subsequent proteosomal degradation (1113). Recent studies in several solid tumor models have shown sensitization to currently used chemotherapeutic agents when combined with new generation HSP90 inhibitors (20, 21). Onalespib, a potent second-generation HSP90 inhibitor differs from other HSP90 inhibitors in its longer duration of target inhibition (22) and its favorable toxicity profile in phase I studies in patients with refractory solid tumors (17).…”
Section: Introductionmentioning
confidence: 99%
“…They bind to the N-terminal ATPase-pocket, affecting the chaperone activity and leading to the depletion of HSP90 substrates by subsequent proteosomal degradation (1113). Recent studies in several solid tumor models have shown sensitization to currently used chemotherapeutic agents when combined with new generation HSP90 inhibitors (20, 21). Onalespib, a potent second-generation HSP90 inhibitor differs from other HSP90 inhibitors in its longer duration of target inhibition (22) and its favorable toxicity profile in phase I studies in patients with refractory solid tumors (17).…”
Section: Introductionmentioning
confidence: 99%
“…Radiosensitization effect in vivo by Hsp90 inhibitors has also been demonstrated (14, 21, 23). These data strongly suggest that targeting Hsp90 with its inhibitors represents a promising strategy for enhancing the sensitivity of cancer cells to radiation (1924). Ganetespib is an investigational small molecule inhibitor of Hsp90 with favorable pharmacologic properties that distinguishes it from other first- and second-generation Hsp90 inhibitors in terms of potency, safety, and tolerability (27, 42).…”
Section: Discussionmentioning
confidence: 95%
“…As Hsp90 inhibitors are known to affect the cell cycle checkpoint (19, 2124, 35, 36), as does irradiation, which causes a G1/S arrest in P53 WT cells (37), we next determined the interaction of radiation with ganetespib on the cell cycle effects in both H460 and A549 cells (Figure 3A–D). G2/M arrest was induced by ganestepib, radiation, and the combination, at 4 hours postirradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…131,204 Several groups have studied Hsp90 involvement in GBM and have proposed that its inhibition is a possible therapeutic measure for direct reduction of glioma tumor growth. 58,154,252,255 Furthermore, current research has focused on the ability of Hsp90 knockdown or inhibition to attenuate the effects of radiation 155,228 and drug therapy 13 through increased cell sensitization, potentially offering a combinatorial and aggressive approach to GBM treatment by using Hsp90 targeting. The RACK1 protein has been shown to be a potent molecular enhancer of tumorigenesis in several types of cancers, making it a potentially viable target for suppressing tumor growth, tumor cell proliferation, and tumor-associated angiogenesis.…”
Section: Heat Shock Protein 90/receptor For Activated C Kinasementioning
confidence: 99%